Epistolary rhetoric in the context of epistolography - Toktagazin, Muratbek B. (Journal of the Belarusian State University. Journalism, 2019)
This article discusses substantiates the innovative introduction of the term «epistolary rhetoric» in the context of the use of rhetoric as a special form of epistolary communication. The author examines the epistolary rhetoric as a particular form of epistolary communication, as the tools and techniques of rhetoric used in the preparation of the content for purposes inherent in the rhetoric is the belief of the interlocutor in something using the written form of a deferred dialogue. Therefore, we need to talk about epistolary rhetoric as the art of persuasion letter. In the modern world, with the development of modern communication technologies, the role of epistolary rhetoric is increasing, as humanity generally passes into the format of written communication in the space of the Internet. The purpose of the study was to explore the concept of rhetoric, its current position among other scientific disciplines, to justify the definition and use of the term «epistolary rhetoric» to identify the role of the epistolary rhetoric in modern written communication. The novelty of the article lies in the fact that to date, the rhetoric has been studied in the context of an applied discipline, many, however, the understanding of the use of epistolary rhetoric in the letter, and especially in modern communication have not been explored. The content of the article will be useful to journalists, historians, researchers of the epistolary genre, literary critics.
Keywords: rhetoric; epistolary communication; epistolary rhetoric; epistolography; neo-rhetoric